Combined event-related fMRI and intracerebral ERP study of an auditory oddball task - Brázdil, Milan; Dobsík, Martin; Mikl, Michal; Hlustík, Petr; Daniel, Pavel; Pazourková, Marta; Krupa, Petr; Rektor, Ivan (NeuroImage, 2005)
Event-related fMRI (efMRI) has been repeatedly used to seek the neural sources of endogenous event-related potentials (ERP). However, significant discrepancies exist between the efMRI data and the results of previously published intracranial ERP studies of oddball task. To evaluate the capacity of efMRI to define the sources of the P3 component of ERP within the human brain, both efMRI and intracerebral ERP recordings were performed in eight patients with intractable epilepsy (five males and three females) during their preoperative invasive video-EEG monitoring. An identical auditory oddball task with frequent and target stimuli was completed in two sessions. A total of 606 intracerebral sites were electrophysiologically investigated by means of depth electrodes. In accordance with the finding of multiple intracerebral generators of P3 potential, the target stimuli evoked MRI signal increase in multiple brain regions. However, regions with evident hemodynamic and electrophysiological responses overlapped only partially. P3 generators were always found within hemodynamic-active sites, if these sites were investigated by means of depth electrodes. On the other hand, unequivocal local sources of P3 potential were apparently also located outside the regions with a significant hemodynamic response (typically in mesiotemporal regions). Both methods should thus be viewed as mutually complementary in investigations of the spatial distribution of cortical and subcortical activation during oddball task.
Keywords: dospělí; Magnetic Resonance Imaging; Evoked Potentials, Auditory; Cerebrovascular Circulation; Epilepsy; Female; Electrodes, Implanted; Adult; sluchové evokované potenciály; ženské pohlaví; Electrophysiology; mozkový krevní oběh; sluchové korové centrum; lidé; magnetická rezonanční tomografie; mozek; Auditory Perception; sluchová percepce; epilepsie; Male; Brain; Oxygen; implantované elektrody; elektrofyziologie; Auditory Cortex; mužské pohlaví; elektroencefalografie; kyslík; Electroencephalography; Humans